USM STUDENTS TO STAY AWAY FROM AREAS PRONE TO THE HIGH-TIDE PHENOMENON - DEPUTY VC - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 October 2016 Universiti Sains Malaysia (USM) has advised its students to stay away from activities in areas that are prone to the hightide phenomenon.